Mechanistic Insights into the Biological Effects and Antioxidant Activity of Walnut (Juglans regia L.) Ellagitannins: A Systematic Review - Letiția Mateș; Roxana Banc; Flaviu Andrei Zaharie; Marius Emil Rusu; Daniela-Saveta Popa (MDPI AG, 2024)
Walnuts (Juglans regia L.) are an important source of ellagitannins. They have been linked to positive effects on many pathologies, including cardiovascular disorders, neurodegenerative syndromes, and cancer. The limited bioavailability of ellagitannins prevents them from reaching significant circulatory levels, despite their antioxidant, anti-inflammatory, and chemopreventive properties. Urolithins are ellagitannin gut microbiota-derived metabolites. They have better intestinal absorption and may be responsible for the biological activities of ellagitannins. Recent evidence showed that walnut ellagitannins and their metabolites, urolithins, could have positive outcomes for human health. This study aims to synthesize the current literature on the antioxidant activity and mechanistic pathways involved in the therapeutic potential of walnut ellagitannins and their metabolites. In the eligible selected studies (n = 31), glansreginin A, pedunculagin, and casuarictin were the most prevalent ellagitannins in walnuts. A total of 15 urolithins, their glucuronides, and sulfate metabolites have been identified in urine, blood, feces, breast milk, and prostate tissue in analyzed samples. Urolithins A and B were associated with antioxidant, anti-inflammatory, cardioprotective, neuroprotective, anticarcinogenic, and anti-aging activities, both in preclinical and clinical studies. Despite the promising results, further well-designed studies are necessary to fully elucidate the mechanisms and confirm the therapeutic potential of these compounds in human health.